Territoires autochtones et revendications au Canada. Les incohérences du discours originaliste en anthropologie et en droit - Leila Inksetter (Droit et Cultures)
In Canada, aboriginal rights are protected by the constitution. These rights take their source in pre-colonial Indigenous cultural and legal systems. They can be mobilized by demonstrating the continuity of an Indigenous cultural practice that existed before European contact. Indigenous ways of life just before European contact therefore become the reference for defining contemporary Aboriginal rights. This originalist conception within the law is mirrored in the field of anthropology, by its historical quest for an original Indigenous essence. The article shows that this concern for an original moment is nevertheless based on contemporary Indigenous social structures projected into the distant past. The article takes as an example the hunting peoples located on the north shore of the St. Lawrence River, focusing on the Algonquins/Anicinabek, the Atikamekw Nehirowisiwok and the Innus/Ilnus. It examines the articulation between family territoriality, expressed through family hunting territories, and collective territoriality mobilized by contemporary Indigenous political organizations. The result leads to the strengthening of Indigenous governmental structures that resemble those of modern states.